Perancangan Desain Taman Luar Pusat Pastoral Sanjaya Muntilan (PPSM) - Sugesti Retno Yanti; Prasasto Satwiko; Lucia Asdra Ludwiarti; Bhanu Rizfa Hakim (Jurnal Atma Inovasia, 2025)
The Sanjaya Muntilan Pastoral Center (PPSM) has excellent potential as a public space that supports spiritual, educational, and social activities. However, limited outdoor facilities and uncomfortable environmental conditions challenge the area's development. This study aims to design an outdoor garden based on sustainable landscape architecture that enhances comfort, ecological value, and social functionality at PPSM. The methods employed include literature review, field observation, SWOT analysis, and thermal comfort simulation using ENVI-met software. The design outcomes include functional zone division, selection of local vegetation, and integration of hardscape–softscape elements. Thermal simulations during peak outdoor activity hours (08:00, 10:00, 16:00, and 18:00 WIB) showed a significant reduction in PET temperatures in key areas, demonstrating the design's effectiveness in creating a more comfortable microclimate. With an ecological and participatory approach, this park is expected to become a green oasis supporting pastoral services and the well-being of the surrounding environment.